Bandpass filter Based on Ring Resonator at RF Frequency above 20 GHz - Norfishah Ab. Wahab; A. Amiruddin; Roskhatijah Radzuan; Zuhaila Mat Yasin; N. A. Salim; N. A. Rahmat; N. F. A. Aziz (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents two dual-mode rectangular ring resonators, designed at RF frequency above 20 GHz for bandpass filter applications. The first resonator is designed at 20 GHz using single layer microstrip technology, on Rogers Duroid TMM10 substrate with the following characteristics; relative dielectric constant (εr) = 9.2, substrate thickness (h) = 1.270 mm, dielectric loss tangent (tan δ) = 0. The second resonator is built using multilayer CMOS technology at 75 GHz. The resonator is simulated using fluorinated silicon glass (FSG) and silicone rich oxide (SRO) with relative dielectric constant (εr) equals to 3.7 and 4.2 respectively. Both filter designs are built using full-wave electromagnetic simulation tool. For filter design using microstrip technology, the return lossis found at 9.999 dB and the insertion lossis at 3.108 dB while for filter design using CMOS technology, the return loss is found at 11.299 dB and the insertion lossat 0.335 dB. Both results had shown good passband performance with high rejection level at the out-of band.